Servant Leadership as a Factor of Social Entrepreneurship - O. S. Vikhanskiy; A. G. Mirakyan (Управленческие науки, 2018)
Subject. The article focuses on two perspective directions of research in theoretical managerial thought. One of the directions is social entrepreneurship that exists in the field of entrepreneurship. The other one is servant leadership that describes an emerging concept in the field of leadership.Purpose. The purpose of the study is to formulate the tasks developing the management theory that is based on the symbiotic relationship between social entrepreneurship and servant leadership.Methodology. The scholars introduce new methodological approach to research and contribute to the conceptual development of management. The authors analyze and consolidate the interconnection and interpenetration of social entrepreneurship and servant leadership.Results. The article provides an overview of the main essence of social entrepreneurship and its general features. They distinguish social entrepreneurship from “traditional” one as well as from other cognate activities like “social activism”. Moreover, the work considers external and internal antecedents influencing the social entrepreneurship development. The following part of the article is devoted to the development of a new avenue in the leadership area. The authors describe fundamental changes in the management paradigm, in particular transformations in the leadership views. The article also addresses the major specifics of the servant leadership ideology and indicates the significance of servant leaders. Finally, the authors focus on the role of servant leadership in social entrepreneurship. They highlight the basic attributes that show the similar value orientations both for servant leader and social entrepreneur.Conclusions. In conclusion, the attempt to find interrelationships of certain directions from the classic management theory would be one of the contemporary trends in management theory development.